THE EFFECT OF COMMUNICATION COMPETENCE ON VISITOR SATISFACTION AT THE DEPARTMENT OF STATEMENT AND ARCHIVES OF MAGELANG CITY - Wiji Safitri; Joko Tri Nugraha (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Optimal public service requires good communication skills from officers. Although the number of visitors to the Magelang City Library and Archives Office continues to increase significantly, there are still complaints from visitors regarding service quality, such as inadequate information and indecisiveness of officers. This indicates a gap in the communication skills of officers that needs to be improved. This study aims to measure the effect of public service communication skills on visitor satisfaction. This study uses an associative quantitative method with an explanatory research approach. Data collection techniques were carried out through questionnaire. The research population consisted of 406,195 visitors with a sample of 150 respondents determined using the Slovin formula and random sampling technique. Data analysis was performed using simple linear regression with the help of the SPSS program. The results showed that communication competence had a positive and significant effect on visitor satisfaction with a coefficient of determination (R²) of 0.700, these findings show that a considerable amount of visitor satisfication can be explained by communication competenc, nevertheless, this influence should be interpreted cautiously because other organizational and service elements that were not examined in this study also have an impact on satisfaction. Theoretically, the results of this study can be used as a reference for further research related to public service communication in the library and archiving sector. Practically, the findings of this study can be used by the managers of the library as material for evaluating and improving services to meet visitors' expectations.